A multimodal couple-coping intervention for enhancing sexual adjustment among breast cancer women: Study protocol for a randomised controlled trial. - Ka Ming Chow; Carmen Wing Han Chan; Kai Chow Choi; Alexandra Leigh McCarthy (PLoS ONE)
Aim To investigate the effects of a multimodal couple-based sexual health intervention for premenopausal women treated for breast cancer and their partners to provide personalised psychosexual care, and to understand participants' experience of, and adherence to, the intervention. Methods This is an assessor-blinded, randomised controlled trial. Premenopausal women treated for breast cancer (N = 160) and their partners will be recruited. Dyads will be randomised into an intervention (n = 80) or attention control (n = 80) group. The intervention group will receive the multimodal couple-based sexual health intervention over eight weeks. The intervention comprises five face-to-face and virtual individual couple counselling sessions combined with online reading, a chat-based discussion forum, and telephone calls. The intervention is based on level I-II evidence and a robust theoretical framework. The attention control group will receive usual care plus telephone calls comprising general greetings and reminders to complete follow-up surveys. Sexual adjustment, relationship quality and quality of life will be measured at baseline, after completion of the intervention, three months and six months post-intervention. The project will adhere to the CONSORT-EHEALTH checklist. Qualitative interviews will explore the participants' experience of, and adherence to, the intervention. Discussion This study will provide the first pragmatic evidence of the effectiveness of a multimodal couple-coping intervention to support premenopausal women and their partners to improve sexuality, relationship quality and quality of life after treatment for breast cancer. Implications for the profession and /or patient care Sexual health is a neglected area in clinical practice, for patients and partners. The ever-growing population of women treated for breast cancer at younger age has created a more pressing need for the development of tailored sexual health interventions. If effective, this intervention could be incorporated into routine cancer care to provide better support and care for this patient population to enhance sexual health, intimacy and overall well-being. Trial registration ISRCTN35481498; prospectively registered on 08/05/2023.